NFT UNDER CONDITIONS OF CRITICAL TRANSFORMATIONS IN THE DIGITAL ASSET MARKET - Svitlana Volosovych; Mariia Nezhyva; Іgor Napadovskyi (Baltic Journal of Economic Studies)
The integration of information technologies into all spheres of human activity, the proliferation of online communities, and the expansion of the virtual world have precipitated a transformation in consumer needs and an influence on their preferences. This paradigm shift has established the foundations for the emergence and development of digital assets, one notable example being the non-fungible token (NFT). The present article aims to examine the prospects for the development of non-fungible tokens (NFTs) in the context of global transformations in the digital asset market. A graphical method was employed in the study to identify global trends in the development of the NFT market. The use of a systematic approach allowed the identification of differences between NFT 1.0 and NFT 2.0. A comparative analysis was conducted to identify the strengths and weaknesses of the functioning of NFTs, as well as the threats and opportunities for the future existence of NFTs. A descriptive literature review allowed the development of optimistic, neutral and pessimistic scenarios for the development of the non-fungible token market. Product, functional and technological approaches to understanding non-fungible tokens were identified. The article examines NFTs in two forms: as digital assets and as digital certificates. The traditional and non-traditional reasons for using NFTs have been clarified. A comparative characterisation of NFT 1.0 and NFT 2.0 was made based on characteristics, ownership, participants, personalisation and areas of use. The article presents an analysis of the NFT market with a focus on its structural changes. The current state of the non-fungible token market is characterised by a shift from speculation to increased utility of NFTs in various sectors. The strengths and weaknesses of the functioning of non-fungible tokens were identified, as well as the threats and opportunities for their development in the context of global transformations. The study allowed the formulation of scenarios for the development of non-fungible tokens in the midst of critical transformations in the digital asset market. Under the optimistic scenario, market capitalisation, trading volumes, the number of users, the share of non-traditional NFT segments, the use of artificial intelligence in the creation of NFTs, the technical modernisation of NFTs and the legal regulation of all related relationships will increase. The neutral scenario will be characterised by volatility in market capitalisation, trading volumes and the number of market participants. In this scenario, regulation will focus on combating fraud and terrorist financing in the NFT market. In a pessimistic scenario, all key market indicators will decline, resulting in losses from non-fungible token transactions. In some jurisdictions, certain types of NFT transactions will be banned. The conclusions emphasise that with the expansion of the virtual world, NFTs are acquiring the characteristics of a digital product with high potential for use in various fields. The development of the NFT market is characterised by a combination of conflicting trends. On the one hand, there has been an increase in NFT capitalisation in early 2025, along with the growth of holders, buyers, and sellers in 2024. Conversely, there has been a decline in NFT trading volumes. These trends may provide the basis for the implementation of an optimistic scenario for the future development of the non-fungible token market.